Training and Guidance for Aksara Jawa Learning for Elementary School Teachers in Sarongan Banyuwangi Village - Susilo, Yohan; Hasan, Latif Nur; Sukarman, Sukarman; Darni, Darni; Listiyapinto, Ravi Zam-zam (ABISATYA : Journal of Community Engagement, 2025)
This community service program aims to enhance the competence of elementary school teachers in teaching Javanese script through training and mentoring activities in Sarongan Village, Banyuwangi. The program was motivated by the limited mastery of Javanese script among teachers, the lack of effective teaching methods, and the declining interest of students in learning traditional scripts. The implementation consisted of two main stages: (1) theoretical and practical sessions delivered face-to-face, covering Javanese script writing and teaching techniques, and (2) mentoring sessions conducted online to guide teachers in applying the knowledge directly in their classrooms. The methods used included lectures, drills, assignments, discussions, and performance-based assessments. The results showed that teachers’ understanding and teaching skills improved significantly, with 70% of participants being able to conduct Javanese script lessons according to proper writing rules. Participants’ responses indicated high satisfaction and increased motivation to integrate Javanese script into their teaching practices. The program not only strengthened the teachers’ capacity but also contributed to the preservation of local cultural heritage in formal education. The output of this program included a training video, media publications, an article, and an Intellectual Property Rights (IPR) registration. These results highlight the importance of continuous capacity building for teachers in remote areas to ensure sustainable cultural education and community empowerment.